DELINEATION OF 3-D SEISMIC VELOCITY STRUCTURE IN BANYUMAS BASIN, CENTRAL JAVA, USING TRAVELTIME TOMOGRAPHY - Hidayat
The Banyumas Basin is a sedimentary basin located in the southern part of Central Java, Indonesia. Several discoveries of oil seepage in the Banyumas Basin are evidence that sourcerock of hydrocarbon has been formed. The volcanic deposits in the study area cause the use of conventional seismic methods is less optimum. To see the thickness of the sediments and also the subsurface geological structure, the Passive Seismic Tomography (PST) method is used to image the subsurface velocity structure of 3-D Vp, Vs and Vp / Vs. The study used 70 borehole seismograph stations with 177 days recording duration. A total of 354 events produced 9,370 Pwave phases and 9368 S-wave phases used for travel time tomographic inversion. The initial velocity model in the shallow crust layer uses Jati-1 well checkshot data contained in the network and has a depth of up to about 4500 m. Resolution test with Checkerboard Resolution Test (CRT), Diagonal Resolution Element (DRE) and Derivative Weight Sum (DWS) shows that the study area can be resolved well. Validation of tomographic inversion results is done using geological research data, residual gravity anomalies, and conventional seismic cross sections. The vertical cross section of the tomographic inversion results shows good compatibility with conventional seismic cross sections and interpreted based on control of Jati-1 wells. Horizontal slice results show good compatibility with regional geological maps, geological structure models and gravity residual anomalies in the study area. Anticline structures that can be structural traps for the Banyumas Basin petroleum system can be imaged well. This method also succeeds in describing the depth of basement which cannot be imaged by conventional seismic methods. Based on the results of this study, the depth of basement is at a depth of 8000m.